2017
DOI: 10.1097/md.0000000000007581
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of postoperative pain between laparoscopic and robot-assisted partial nephrectomies for renal tumors

Abstract: Robot-assisted partial nephrectomy (RAPN) has emerged as an alternative to laparoscopic partial nephrectomy (LPN) for removal of renal tumors. Several advantages of robotic surgery have been reported, but there is no comparative study on postoperative pain between the 2 techniques. Therefore, we compared the postoperative numerical rating scale (NRS) of pain intensity between patients who underwent LPN and those who underwent RAPN.We included 705 patients who underwent either LPN (n = 200) or RAPN (n = 505) fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 17 publications
(20 reference statements)
1
8
0
Order By: Relevance
“… 1 , 2 However, despite less surgical trauma with LRS compared with open surgery, moderate-to-severe pain remains in the early postoperative period. 3 , 4 Adequate pain control is important for rapid recovery after surgery. Although opioids are the most commonly used analgesics, they bring side effects such as postoperative nausea and vomiting, gastro-intestinal ileus and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 However, despite less surgical trauma with LRS compared with open surgery, moderate-to-severe pain remains in the early postoperative period. 3 , 4 Adequate pain control is important for rapid recovery after surgery. Although opioids are the most commonly used analgesics, they bring side effects such as postoperative nausea and vomiting, gastro-intestinal ileus and respiratory depression.…”
Section: Introductionmentioning
confidence: 99%
“…They demonstrated that the morphine consumption and pain scores at 24 hours after surgery were comparable. A propensity score matching analysis has reported that postoperative pain was not significantly different between the different operation mode (robot-assisted partial nephrectomy vs laparoscopic partial nephrectomy) [35]. A third arm in our study may have been beneficial in discerning whether the QLB has assistant effects when compared to"no block" pattern.…”
Section: Discussionmentioning
confidence: 70%
“…Jin et al reported no significant difference in postoperative pain between patients who underwent RAPN and laparoscopic partial nephrectomy. The NRS scores in the RAPN group anesthetized by general anesthesia only were 5.9, 3.5, and 2.8 at POD 0, 1, and 2, respectively [11].…”
Section: Discussionmentioning
confidence: 87%